Biodiversity of Tree Species: Composition and Structure in Raden Soerjo Grand Forest Park, Batu, East Java, Indonesia - Khoirunnisa, Khoirunnisa; Wisanti, Wisanti; Indah, Novita Kartika; Iman, Muhamad Hilmi Ihsanul; Ullah, Lisa Rohmatul (Al-Kauniyah: Jurnal Biologi, 2026)
Raden Soerjo Grand Forest Park is a conservation area in East Java with moderate tree diversity. This study analyzed the diversity, composition, and structure of trees in three vegetation types: open forest, closed forest, and post-fire forest. Data collection used a systematic sampling method with random start. Data in the form of tree species names and numbers of individuals were analyzed to determine the ecological index and Canonical Correspondence Analysis (CCA). A total of 25 species from 21 families were identified, with Fagaceae and Lauraceae dominating in open and closed forests, and Casuarinaceae in post-fire forest. Lithocarpus sundaicus showed the highest Importance Value Index in open and closed forests, while Casuarina junghuhniana dominated the post-fire forest. Pioneer species such as Homalanthus populneus, Ficus hispida, and C. junghuhniana were present in all vegetation types. The diversity index showed moderate diversity (1.79 and 2.09), low species richness (2.22 and 3.45), and high evenness (0.69 and 0.71) in open and closed forests. Tree distribution is dominated by the 61–80 cm diameter class in open and closed forests, and 41–60 cm in post-fire forests. CCA showed that light intensity, soil moisture, air temperature, and soil pH influence species distribution. Four species are endemic to Indonesia, with three species of conservation concern: Lithocarpus korthalsii and Canthiumera glabra (near threatened), and Saurauia bracteosa (vulnerable).